Risk Factors Analysis Of Surgical Site Infection (SSI) Incident In Post Emergency Cesarean Section At Ulin Hospital Banjarmasin 2020-2022 - Pribakti Budinurdjaja; Hermin Sabaruddin; Bambang Abimanyu; Agatha Vamela (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2024)
Surgical site infection (SSI) is a common complication in obstetric surgery, especially cesarean section (CS). This procedure can be carried out electively or as an emergency. Compared to elective CS, emergency CS has a higher risk of SSI. The occurrence of SSI during an emergency CS is thought to be related to several factors, including host, pregnancy, delivery, and procedure. Analysis of the relationship between these factors and the incidence of SSI is very important to study. The aims of the study for analyzing factors related to the incidence of SSI in emergency CS at Ulin Hospital Banjarmasin for the period of 2020-2022. This research is an analytical observational study with a cross sectional approach. The entire research was conducted at the Ulin Banjarmasin Regional General Hospital (RSUD) in January-May 2023. The subjects were pregnant women who underwent emergency CS in the 2020-2022 period. Data on clinical characteristics and obstetric risk factors were taken from medical records and the incidence of SSI was calculated as a percentage. Next, the data results were analyzed using the Chi-Square test. The results of the study showed that there were 1271 emergency CS with an overall SSI incidence rate of 1.5%. The results of the analysis showed that there was a relationship between age, parity, history of previous CS, history of Antenatal Care (ANC), and type of incision on the incidence of SSI (P<0.05). The incidence of SSI in emergency CS at Ulin Banjarmasin Regional Hospital for the 2020-2022 period is 1.5%. The SSI that occurs is thought to be related to the mother's age at pregnancy, parity, history of previous CS, history of ANC, and type of incision.